Tubal mesosalpinx cysts combined with adnexal torsion in adolescents: a report of two cases and review of the literature - Junzhuo Chen; Changjun Li; He Zhang; Dongqi Li; Wei Wang (BMC, 2024)
Abstract Background Tubal mesosalpinx cysts are paratubal cysts, that account for approximately 10% of adnexal masses, and the presence of these cysts combined with adnexal torsion is a rare acute abdominal condition, with few cases reported in the literature. We reported two cases of adolescent tubal mesosalpinx cysts combined with adnexal torsion and reviewed the literature to help improve the diagnosis of the disease. Case reports The first patient was an 11-year-old girl with left lower abdominal pain for 5 days and fever with nausea and vomiting for 3 days, who was found to have a cystic pelvic mass on preoperative imaging and was diagnosed intraoperatively and postoperatively on pathology as having a left tubal mesosalpinx cyst combined with adnexal torsion. The second patient was a 13-year-old girl with right lower abdominal pain for 16 h and a palpable mass in the lower and middle abdomen on examination, which was hard and tender to palpate. Preoperative imaging revealed a large cystic mass in the right adnexal region, and intraoperative and postoperative pathology revealed a right tubal mesosalpinx cyst combined with adnexal torsion. Conclusions Tubal mesosalpinx cysts combined with adnexal torsion are rare causes of acute lower abdominal pain. Early diagnosis and timely surgery are necessary to ensure ovarian and tubal function. Accurate preoperative imaging diagnosis is challenging, and MRI is a beneficial supplement to ultrasound and CT examinations, providing more objective imaging information and reducing the incidence of adverse outcomes.